A novel variant in SIAH1 associated with autosomal dominant Buratti-Harel syndrome - Zheng, Hong; Zhang, Lan; Li, Fuwei (Frontiers in Neuroscience, 2026)
IntroductionBuratti-Harel syndrome (BURHAS) is a rare autosomal dominant neurodevelopmental disorder caused by SIAH1 (Siah1 E3 ubiquitin ligase) variants, characterized by infantile hypotonia, global developmental delay, and variable multisystem involvement. To date, 13 pathogenic SIAH1 variants have been reported in 13 patients, but the functional and phenotypic implications of mutations in the SIAH1 zinc finger domain remain poorly characterized. This study included a Chinese pediatric patient with unexplained neurodevelopmental and multisystem abnormalities.MethodsTrio whole-exome sequencing (WES) was performed to identify potential causative variants. Structural modeling was used to analyze the impact of the identified variant on SIAH1 protein structure. Additionally, a comparative genotype-phenotype analysis was conducted on 14 genetically confirmed BURHAS cases (including the present patient).ResultsA de novo missense variant [c.288C > G (p.Phe96Leu)] in the zinc finger domain of SIAH1 was identified in the patient. Structural modeling revealed that this variant destabilized the zinc finger domain (DDG = –2.09 kcal/mol), which may disrupt the ZnF-1 domain function by impairing zinc ion-mediated structural stability. Comparative analysis of 14 genetically confirmed cases (including this study) demonstrated a genotype-phenotype correlation: zinc finger domain variants (n = 4) exhibited broader phenotypic heterogeneity compared to RING domain variants (n = 7), which were enriched for severe developmental delay and reproductive anomalies.DiscussionThis study expands the mutational spectrum of SIAH1-associated disorders. We advocate for the inclusion of SIAH1 in diagnostic panels for patients with unexplained neurodevelopmental disorders and multisystem dysmorphisms.